2001
DOI: 10.1007/s001340100949
|View full text |Cite
|
Sign up to set email alerts
|

Massive elevation of procalcitonin plasma levels in the absence of infection in kidney transplant patients treated with pan-T-cell antibodies

Abstract: PCT monitoring for evaluating infectious complications in kidney transplant patients must be very careful during pan-T-cell antibody therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
36
1
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 0 publications
5
36
1
2
Order By: Relevance
“…[9][10][11] This evidence is confirmed and broadened by our data derived from paediatric patients with haematological or oncological diseases.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…[9][10][11] This evidence is confirmed and broadened by our data derived from paediatric patients with haematological or oncological diseases.…”
Section: Discussionsupporting
confidence: 75%
“…[4][5][6][7][8] However, there are sporadic reports on high PCT levels in adult patients after T-cell antibody infusion following kidney transplantation with no evidence of infection. [9][10][11] To further investigate these observations, we analysed the characteristics of PCT and CRP serum levels in paediatric patients with haematological or oncological diseases during treatment with T-cell antibodies and compared these with those occurring with episodes of Gram-negative sepsis. Furthermore, the roles of cytotoxic chemotherapy, irradiation and blood products were examined in the context of other potential stimuli for the release of these parameters.…”
mentioning
confidence: 99%
“…(91)(92)(93)]. Its implication in the cytokine cascade stems from demonstrated increases of TNF␣ before increases in PCT (54,94 ) and a documented correlation between the concentrations of these biomarkers (r ϭ 0.86) (35 ). Furthermore, a study involving in vivo LPS stimulation showed an exponential increase over the period 2-6 h after injection, with a plateau from 8 to 24 h (54 ).…”
Section: Biomarker Detectionmentioning
confidence: 99%
“…Additionally, gram-positive and gram-negative organisms cause increases in PCT concentrations that are not significantly different (37,38,78,88 ). However, the definitive evidence of the role of PCT in immune response has been offset by contradictory reports of increased concentrations attributable to various inflammatory insults, including hepatic dysfunction (38 ), trauma (increases within 3 h of trauma) (43,96 ), anti-T-cell therapy (57,94 ), burns, heat stroke, and fungal infection (36 ) [for the exclusion criteria, see Ref. (92 )].…”
Section: Biomarker Detectionmentioning
confidence: 99%
“…Indeed, interferon-␥ inhibits IL-1␤-induced calcitonin mRNA expression (15). Conversely, massive serum PCT elevations have been reported after administration of pan-T cell antibodies (16,17).…”
mentioning
confidence: 99%